SUPPLY CHAIN MAPPING AND ADDED VALUE ANALYSIS OF CORN COMMODITIES IN TANAH LAUT REGENCY - Raden Rizki Amalia; Nina Hairiyah; Nuryati nuryati (BPFP Faperta UNIB, 2020)
Kabupaten Tanah Laut is one of the districts in South Kalimantan Province which has the largest of corn production compared to other districts. Based on data from the Office of Horticultural Food Crops and Plantation of Tanah Laut Regency, it was found that the production of corn commodities from 2017 to 2019 increased. This happens because the demand for corn commodities continues to increase every year. In addition, in Tanah Laut Regency, two large animal feed companies have been established that require corn as the main raw material. The magnitude of this potential makes it necessary to identify entities through supply chain mapping so that the added value of each entity can be determined. The purpose of this research was to map the supply chain and analyze the added value of corn commodity supply chain in Tanah Laut Regency. The research method used in analyzing the supply chain is descriptive analysis using purposive sampling and snowball sampling to obtain in-depth and objective information. Meanwhile, value added analysis uses the Hayami method.The results showed that there were three supply chain entities to reach consumers, namely farmers, small collectors, and large collectors. Meanwhile, the results of the analysis of the added value of each entity obtained the highest value, namely the large collectors with a value added ratio of 87% of Rp. 783,840.00, small collectors with a ratio of 86.4% of Rp. 699,840.00 and farmer entities of 86.13% with a value of Rp. 671,840.00. This is because the treatment of corn commodities in each entity is different.